N-doping TiO2 hollow microspheres with abundant oxygen vacancies for highly photocatalytic nitrogen fixation - Li, Chang; Gu, MengZhen; Gao, MingMing; Liu, KeNing; Zhao, XinYu; Cao, NaiWen; Feng, Jing; Ren, YueMing; Wei, Tong; Zhang, MingYi (Journal of colloid and interface science, 2022)
Design route for enhancing nitrogen reduction performance. [Display omitted] •N-doping extends the light absorption range to the visible light region.•Oxygen vacancies promote the absorption and activation of N2.•The high ammonia yield rate of N-doping TiO2 is 80.09 μmol gcat−1h−1. Photocatalytic fixation of nitrogen to ammonia (NH3) is a green but low-efficiency technology due to the high recombination of photo-generated carriers and poor light absorption of photocatalysts. Generally, the adsorption capacity for N2 and the band position of TiO2 are responsible for bandgap, light-adsorption, and the separation of photocarriers. Therefore, they play crucial roles to improve catalytic activity. Herein, N-doping TiO2 hollow microspheres (NTO-0.5) with oxygen vacancies were synthesized via a hydrothermal method using phenolic resin microsphere as a template. The obtained NTO-0.5 achieves an impressive ammonia yield of 80.09 μmol gcat−1h−1. Oxygen vacancies of NTO-0.5 were confirmed by ESR, Raman, XPS, Zeta potential, and H2O2 treatment for reducing oxygen vacancies. The ammonia yield of NTO-0.5 decreases to 34.78 μmol gcat−1h−1 after reducing oxygen vacancies by H2O2 treatment, which demonstrates the importance of oxygen vacancies. The oxygen vacancies narrow the bandgap from 3.18 eV to 2.83 eV and impede the recombination of photo-generated carriers. The hollow microspheres structure is conducive to light absorption and utilization. Therefore, the synergistic effect between the oxygen vacancies and the hollow microspheres structure boosts the efficiency of photocatalytic nitrogen fixation. After four cycles, the ammonia production yield still maintains at 76.52 μmol gcat−1h−1, meaning high stability. This work provides a new insight into the construction of catalysts with oxygen vacancies to enhance photocatalytic nitrogen fixation performance.